A rare case of Guillain-Barré syndrome in pregnancy and its implications: a case report - Mohanty, Girija S.; Kumar, Abhay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Guillain barre syndrome (GBS) is a rare neurological disease in pregnancy. Incidence varies from 1.2 and 1.9 cases per 100,000 people annually. It carries high maternal risk and may complicate pregnancy. It usually presents as an acute ascending symmetrical polyneuropathy. It requires early diagnosis and multidisciplinary supportive care for its management.